Feasibility of a remotely-delivered yoga intervention on cognitive function in breast cancer survivors: a mixed-methods study - Neville, Alyssa R.; Bernstein, Lori J.; Sabiston, Catherine M.; Jones, Jennifer M.; Trinh, Linda (Frontiers in Cognition, 2023)
Background: Cancer-related cognitive impairment (CRCI) is a common, persistent quality of life complaint among breast cancer survivors (BCS), however there remain no proven treatments. There is emerging evidence that aerobic exercise and yoga may improve CRCI. There remains limited research on the safety and feasibility of virtually-supervised, remotely-delivered yoga interventions among cancer survivors, and no yoga studies to date have assessed cognitive function as a primary outcome in BCS. The purpose of this study was to explore the feasibility of an 8-week, remotely-delivered yoga intervention and examine its impact on cognitive function, fatigue, and exercise levels in BCS using a concurrent mixed-methods design. Methods: Participants completed objective and self-report cognitive function measures (NIH Toolbox remote cognitive battery, PsyToolkit Task Switch test, Functional Assessment of Cancer Therapy-Cognitive Function); fatigue (Revised-Piper Fatigue Scale); and exercise activity level (modified Godin Leisure Time Exercise Questionnaire) before and after the yoga intervention. Semi-structured qualitative interviews were conducted post-intervention to understand participants' experiences with the yoga intervention, CRCI, and fatigue. Results: The intervention surpassed a priori feasibility indicators (adherence rate = 83.7%, attrition rate = 5.4%, no adverse events). Participants (N=18, Mage=52.2 ± 10.1) had significant improvements in objective memory, fatigue, and weekly minutes of moderate-to-vigorous exercise postintervention. Qualitative themes indicated that participants found the remote intervention to be enjoyable and beneficial. Conclusions: In this small proof-of-concept study, remotely-delivered yoga appears safe and effective at improving CRCI. Future randomized controlled trials examining the impact of remotely-delivered yoga interventions on cognitive function in BCS are warranted.